2005
DOI: 10.3748/wjg.v11.i3.403
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant status in colorectal cancer

Abstract: Colorectal carcinogenesis is associated with serious oxidative stress and confirms that gradual advancement of oxidative-antioxidative disorders is followed by progression of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
136
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(163 citation statements)
references
References 25 publications
20
136
2
5
Order By: Relevance
“…Although our results confirm the previous findings, we observed a sharp increase in lipid peroxide adducts in stage IV of CRC. Our results are also in agreement with the reported deployment in stage IV CRC of nonenzymatic antioxidants such as GSH and vitamins C and E [41].…”
Section: Oxidation State Of Crc Along Stages and Its Relationship To supporting
confidence: 93%
See 2 more Smart Citations
“…Although our results confirm the previous findings, we observed a sharp increase in lipid peroxide adducts in stage IV of CRC. Our results are also in agreement with the reported deployment in stage IV CRC of nonenzymatic antioxidants such as GSH and vitamins C and E [41].…”
Section: Oxidation State Of Crc Along Stages and Its Relationship To supporting
confidence: 93%
“…The transcriptional responses of ROS-dependent genes parallel or oppose ApoD expression changes throughout the stages of CRC We observe a general upregulation of antioxidant gene expression when comparing CRC and control tissues, as it has been previously described [41,46]. It accounts for the timely cell response to cope with the increasing levels of oxidative stress generated by the abnormal proliferation of cancerous cells.…”
Section: Oxidation State Of Crc Along Stages and Its Relationship To supporting
confidence: 64%
See 1 more Smart Citation
“…One hypothesis is that it does so via antioxidant activity. Recent studies indicate that a high level of catalase expression could be associated with less genetic damage, thereby reducing the risk of CRC 29 and the oxidative stress generated by DMH. However, we observed no difference in the expression of catalase in the liver and intestine following the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that gradual advancement of oxidative-antioxidative disorders is followed by progression of colorectal cancer [34]. In considering a critical function for oxidative stress in progression of colorectal cancers, regulation of the activities of H2O2 metabolizing enzymes, such as superoxide dimutase (SOD), catalase and glutathione peroxidase (GPx) are likely to be required [34]. Among the anti-oxidants, catalase is a heme-containing peroxisomal enzyme and protects the H2O2 generated in normal human tissues [27].…”
Section: Introductionmentioning
confidence: 99%